KEEFEKTIFAN PEMBELAJARAN MODEL ELICITING ACTIVITIES (MEAs) UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS DAN MENGURANGI KECEMASAN SISWA - Ade, Andreas; Mirza, Ade; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the ability of mathematical representations and determine the level of student anxiety in learning mathematics in the materials of circumference and wide of a rectangular and trapezoidal on the seventh grade student of SMP Kristen Marantha Pontianak. The researcher uses quasi-exsperimental research method and applies control group pre-test and post-test design. The sample of this research are 39 students as exsperimental group and 40 students as control group. The result of data analysis shows that the mean of the gaint-test score of the students mathematical representations ability group is 42,25 and the mean of the gain-test score of control group is 31,55. It is indicate that the mean of gain-test score of the student mathematical representations ability of exsperimental group which given by Model Eliciting Activities (MEAs) is better than the control group which is only given the conventional learning. Whereas the level of student anxietyÂ after given the learning ability by using Model Eliciting Activities (MEAs) is categorized lower.Â Keywords: mathematical representations, model eliciting activities, anxiety.